An awareness and prevalence study of Irish cold-water athletes and external auditory canal exostoses. Issue 7 (7th July 2022) - Boyle, S; Keane, R; Jinih, M; McCarthy Deering, E; Patil, N; Choo, M
Abstract: Objective: This study aimed to determine the awareness, otological symptoms and prevalence of external auditory canal exostoses in Irish cold-water athletes. Method: An online and in person cross-sectional survey was undertaken with Irish cold-water athletes to explore athletes' awareness, known prevalence of external auditory canal exostoses and attitudes towards preventive measures. Results: Of the 926 participants surveyed, 67.5 per cent were aware of external auditory canal exostoses. Triathletes reported the lowest awareness (39.9 per cent) among water athletes. A total of 9.7 per cent ( n = 90) had previously been diagnosed with external auditory canal exostoses and 46.7 per cent ( n = 42) were non-surfers. Ear symptoms were reported in 76 per cent of athletes. Otoscopic examinations showed that 23.7 per cent had external auditory canal exostoses, 3.6 per cent of whom were aware of their diagnosis. Conclusion: The majority of Irish surfing athletes are aware of external auditory canal exostoses. There is less awareness with regard to Ireland's newly emerging sports such as open water swimming and triathlons. Over 90 per cent of athletes surveyed had no idea they had external auditory canal exostoses, which highlights the need to increase public awareness.